2014
DOI: 10.1111/jac.12057
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar Specific Response of CO2 Fertilization on Two Tropical Mung Bean (Vigna radiata L.) Cultivars: ROS Generation, Antioxidant Status, Physiology, Growth, Yield and Seed Quality

Abstract: Increasing atmospheric carbon dioxide concentration (CO2) is an important component of global climate change that will have a significant impact on the productivity of crop plants. In recent years, growth and yield of agricultural crop plants have been shown to increase with elevated CO2 (EC) and have enticed considerable interest due to variation in the response of crop plants. In this study, comparative response of two mung bean cultivars (HUM‐2 and HUM‐6) was evaluated against EC at different growth stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 61 publications
(102 reference statements)
1
14
0
Order By: Relevance
“…Elevated CO 2 may increase the levels of antioxidants, including polyphenols, ascorbate (ASC), alkaloids, and some antioxidant enzyme activities (such as CAT and SOD), with a significant enhancement in the antioxidant capacity, leading to declines in the ROS levels ( Mishra and Agrawal, 2014 ; Zinta et al, 2014 ). For example, when the plants were exposed to elevated CO 2 , increases in the ASC and phenol levels were obtained in Beta vulgaris ( Kumari et al, 2013 ), and increases in the ASC, glutathione (GSH), and ASC/GSH, as well as in their redox status, were found in L. perenne and M. lupulina ( Farfan-Vignolo and Asard, 2012 ).…”
Section: Responses Of Critical Biological Processes To Elevated Co mentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated CO 2 may increase the levels of antioxidants, including polyphenols, ascorbate (ASC), alkaloids, and some antioxidant enzyme activities (such as CAT and SOD), with a significant enhancement in the antioxidant capacity, leading to declines in the ROS levels ( Mishra and Agrawal, 2014 ; Zinta et al, 2014 ). For example, when the plants were exposed to elevated CO 2 , increases in the ASC and phenol levels were obtained in Beta vulgaris ( Kumari et al, 2013 ), and increases in the ASC, glutathione (GSH), and ASC/GSH, as well as in their redox status, were found in L. perenne and M. lupulina ( Farfan-Vignolo and Asard, 2012 ).…”
Section: Responses Of Critical Biological Processes To Elevated Co mentioning
confidence: 99%
“…Moreover, with a delay in the onset of senescence and/or severe stress under elevated CO 2 conditions, it is suggested that the antioxidant profiles, such as the accumulation of antioxidant compounds and antioxidant enzyme activity, may show better performance in dealing with the biological process of senescence ( Hodges and Forney, 2000 ). For instance, a reduction in the oxidative stress under elevated CO 2 was found in Zingiber officinale ( Ghasemzadeh et al, 2010 ), Catharanthus roseus ( Singh and Agrawal, 2015 ), a temperate grassland shrub, Caragana microphylla ( Xu et al, 2014 ), a bean, Vigna radiate ( Mishra and Agrawal, 2014 ), and A. thaliana plants ( Zinta et al, 2014 ).…”
Section: Responses Of Critical Biological Processes To Elevated Co mentioning
confidence: 99%
See 1 more Smart Citation
“…In mung bean, increased [CO 2 ] significantly reduced the percentages of palmitic and omega-6 fatty acids in mature grains, but increased omega-3 fatty acids and the relative proportion of omega-3 to omega-6 fatty acids(Table 6).63 Significant reduction in grain protein, by 1.4%, was noted in soybean at elevated [CO 2 ] 134. Under elevated [CO 2 ], soluble protein and reducing sugar contents declined while total soluble sugars and starch increased in mung bean 135.…”
mentioning
confidence: 99%
“…Apart from carbon metabolism, changes in CO 2 atmospheric levels have been reported to have a positive impact on plant defense mechanisms against oxidative damage by increasing antioxidant capacity (Mishra & Agrawal, ; Zinta et al., ). Farfan‐Vignolo and Asard () reported in perennial ryegrass exposed to elevated CO 2 concentrations that both pronounced increases and decreases were observed in the components of the ascorbate/glutathione cycle.…”
Section: Effects Of Elevated Co2 On Cool‐season Grass Metabolismmentioning
confidence: 99%